2017
DOI: 10.1186/s40885-017-0067-z
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive response to exercise and exercise training in hypertension: odd couple no more

Abstract: The diagnostic and prognostic implication of exaggerated blood pressure response to exercise has been controversial, with opinions ranging from a benign process to a harbinger of potential cardiovascular morbidity. Nonetheless, lowering of blood pressure and prevention of hypertension is in first instance preferable by lifestyle changes, and many studies have shown the inverse association between physical activity level and the incidence of cardiovascular diseases suggesting low aerobic fitness as a strong pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…High BP is a risk factor for disability and mortality from cardiovascular disease ( Jafar et al, 2017 ). Its reduction and the prevention of hypertension are in the first instance preferable through lifestyle changes ( Caldarone et al, 2017 ). The current study has adopted a multicomponent training method because of the different components integrated, in agreement with ACSM guidelines ( Chodzko-Zajko et al, 2009 ; Garber et al, 2011 ) that support many benefits of this training modality on cardiovascular health ( Moraes et al, 2012 ; Neves et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…High BP is a risk factor for disability and mortality from cardiovascular disease ( Jafar et al, 2017 ). Its reduction and the prevention of hypertension are in the first instance preferable through lifestyle changes ( Caldarone et al, 2017 ). The current study has adopted a multicomponent training method because of the different components integrated, in agreement with ACSM guidelines ( Chodzko-Zajko et al, 2009 ; Garber et al, 2011 ) that support many benefits of this training modality on cardiovascular health ( Moraes et al, 2012 ; Neves et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…This may result from a worsening of metabolic risk factors, particularly, HTN, diabetes mellitus, and high cholesterol. The only approach to stop this trend is to target these risk factors through public health initiatives [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies, however, reported that EIH is linked to the future development of hypertension [ 10 , 11 ]. Currently, it has been determined that EIH is an independent risk factor for cardiovascular events and mortality, left ventricular (LV) hypertrophy, and cardiac injury, leading to arrhythmias, atrial fibrillation, myocardial fibrosis, and sudden cardiac death [ 12 , 13 ]. Interestingly, a very recent study has shown that EIH may be associated with a 3.6-fold increased risk of hypertension in highly trained athletes [ 6 ].…”
Section: Introductionmentioning
confidence: 99%